Patients’ perceptions of male and female nursing interns in Guangdong and Guangxi, Southern China - Jun-Juan Liao; Ming Zhou; Xiao-Lan Zeng; Xing-Xing Su; Xiao-Qin Qiu (Medicine, 2026)
Nursing remains female-dominated globally, with gender stereotypes hindering workforce diversity. Male nurses account for 2% to 5% of China’s nursing workforce, and Guangdong/Guangxi lack studies on patients’ perceptions of male nursing interns. This study aims to explore relationships between gender stereotypes, patient satisfaction, and willingness to receive care from male/female nursing interns in Guangdong/Guangxi and identify influencing factors. In this study, a multicenter cross-sectional survey (Mar–Jun 2025) enrolled 460 inpatients from 4 tertiary hospitals (2 each in Guangdong/Guangxi) using a culturally adapted questionnaire. Data were analyzed via descriptive statistics, t -tests, Pearson’s correlation, and multiple linear regression. Results showed that patients had moderate-to-high willingness to accept male ( M = 3.65, SD = 1.08) and female ( M = 4.10, SD = 0.80) interns, with higher willingness for females ( t = 8.53, P < .001). Patient satisfaction was positively correlated ( r = 0.4 < 0.001), while “empathy as feminine” stereotype was negatively correlated ( r = −0.40, P < .001) with male intern acceptance. Multiple linear regression identified satisfaction (β = 0.35), the stereotype (β = −0.29), urban–rural background (β = 0.16), and education (β = 0.13) as predictors (32.7% variance explained). Male, urban, higher-educated patients had higher willingness; no ethnic differences existed. In conclusion, high-‑quality care was related to lower gender bias, while empathy stereotypes correlated with poorer acceptance. Urban–rural and educational factors were associated with perceptions. Targeted education, clinical training, and gender‑sensitive policies were linked to better acceptance and workforce diversity.